EFEKTIFITAS Bill KELOR (Moringa oleifera), Bill SALAK (Salacca zalacca), DAN BIll PEPAYA (Carica papaya) SEBAGAI BAHAN KOAGULAN DALAM MENURUNKAN KEKERUHAN AIR - Intan Permata; Margono .; Ngadino . (GEMA LINGKUNGAN KESEHATAN, 2013)
Water purification is typically carried out using chemical coagulants like Tewes. localname for Aluminum sulfate. In many parts of the world experts are looking into coagulantmaterials derived from plants. Among many of them is the Moringa seeds. Moringa seedscontain water-soluble proteins, when crushed and dissolved in water it will form a positivelycharged solution. Electrophoreses Test proved that positively charged solution were alsoresulted from the use of Salak seeds and Papaya seed. The purpose of this study was toanalyze the differences in coagulation using Moringa (Moringa oleifera), Salak (Salaccazalacca), and Papaya seeds (Carica Papaya).The study was performed in a quasi-experimental set up exercising a pretest-posttestdesign. The object for the study was water sample taken from a river used by the communityin kecamatan Krembung for their water source. As much as 1000 ml of river water was used ineach test run. Test containers were treated with natural coagulants. Coagulant materials usedin the tests were Tawas powder, Moringa, Salak, and Papaya seeds at a dose-series of 50 ppmto 1000 ppm. The resulted data were analyzed using Kruskal - Wallis Test.There was a significant difference with regard to optimal dose of the natural coagulantsas well as the percentage of turbidity reduction. The optimal dose for Moringa seeds was 130ppm with a percentage of reduction at 97,3% that reduced turbidity down to 2.7 NTU. Theoptimal dose for Salak seeds was 100 ppm that resulted in a percentage reduction of 89,2%and reduced the turbidity down to 10.9 NTU. The optimal dose for Papaya seeds was 50 ppmwith a percentage of decline at 83,4% reducing the turbidity down to 16,7 NTU. Moringaseeds coagulant has maximum turbidity reducing capability, while the other two naturalcoagulants, Salak and Papaya seeds, were not in their maximum levels of turbidity reducingcapabilities.At a dose of 200 ppm Moringa seeds exhibited a greater ability as a coagulant inlowering water turbidity compared to the other natural coagulants, Salak seeds at a dose of100 ppm and Papaya seeds at a dose of 50 ppm. The study concluded that Moringa seeds canbe applied as a substitute for chemical coagulants provided they are used within 1 x 24 hours.Key Words : Turbidity and Coagulant